Pengembangan Media Pembelajaran MONOPEKS (Monopoli Eksponen) pada Materi Eksponen Kelas X SMA - Ragilita Rohmani; Janet Trineke Manoy (MATHEdunesa, 2026)
This research aims to describe the process of developing MONOPEKS learning media on exponential material for class X SMA and the results of its development in terms of valid, practical and effective criteria. This research refers to the ADDIE development model which consists of 5 stages, namely the analysis stage focuses on defining instructional problems, learning goals and objectives, the design stage of the initial preparation of media designs and determining assessment instruments, the development stage of the process of making media and validating media, materials and pre-test and post-test by two validators, the implementation stage was tested on 18 class X students of SMA Negeri 1 Puri in Mojokerto, and the evaluation stage was based on research results, the learning media developed met valid criteria based on the results of the overall percentage validation by media experts 84 .4% and 82.5% material from the range of 0% - 100%, so that this media is included in the valid category. This learning media is said to be practical based on the results of filling in the student response questionnaire showing that the average overall score obtained is 93.56% from the range 0% - 100%, so that this media is included in the positive category. This learning media also meets the criteria for effectiveness based on the pre-test and post-test values which are analyzed using the N-gain formula and the results show an average overall score of 0.8096 with effective criteria.